Robustness of BGAs: Parametric study of voids' distribution in SAC solder joints. (November 2019) - Pin, S.; Gracia, A.; Delétage, J.Y.; Fouquet, J.; Frémont, H.
Abstract: The impact of voids on the mechanical behaviour of a BGA solder joint can be evaluated by simulation. The Finite Element (FE) method is adapted to achieve such a task where an infinite number of different void distributions is possible. A tool is proposed in this paper with a modelling process involving a global calculation of a thermal load and a refined sub model. The global model represents a quarter of an electronic package soldered to a piece of PCB while the submodel is limited to a single ball with copper pads and defects under investigation i.e. intermetallic compounds (IMC) and voids. Creep properties are taken into account to model mechanical response of the lead-free solder SAC 305. The simulation of a thermal cycle is performed on the global model with only elastic properties. The nodal displacements are extracted from the results to be applied to the submodel's mesh. True viscoplastic mechanical behaviour is simulated in this refined model to get the solder material response with respect to different defects' considerations. The void distribution is handled with 4 parameters driving the height and thickness of the layer of distribution, the size and the proximity of voids. Simulating the effects of these parameters can afford to sort them for future reliability assessments via Finite Element methods.